Pengaruh Environment Social Governance (ESG) Score Terhadap Kinerja Keuangan Perusahaan Yang Terindeks IDX ESG Leader Tahun 2020-2023 - Wahyu Anggraini, Puri; Darma Rosmala Sari, Tri (Journal of Accounting and Finance Management, 2024)
This study aims to analyze the effect of ESG Score on the financial performance of companies indexed by IDX ESG Leader in 2020-2023. This study uses a purposive sampling method for sampling. The population of this study is companies indexed by IDX ESG Leader in 2020-2023. The data obtained in this study were 10 companies indexed by IDX ESG which were used as research samples with an observation period of 2020-2023. The data source used in this study came from the official website of the company indexed by IDX ESG Leader. The data analysis technique in this study used simple linear regression analysis with the help of SPSS 25. In 2020-2023, assessing company performance based on information from the company's financial statements alone was not enough for stakeholders in making decisions. Stakeholders need other information such as non-financial information, namely the economic, environmental, and social aspects contained in the sustainability report. The results of this study are that ESG Scores have an impact on the financial performance of companies listed on the IDX ESG Leader index in 2020-2023.